Young Children playing together: A choice of engagement. Issue 1 (2nd January 2018) - Anderson, Babs
ABSTRACT: This article highlights the findings of an empirical research project, using an ethnographic approach, taking place over one academic year. It investigates the different forms of engagement that children may present, when acting in free play situations in a nursery in NW England, without direct adult intervention. This range of engagement includes passive, intermittent and two forms of cooperative play, termed divergent and convergent. In the latter, children developed collaborations, using inter-subjectivity, through a series of phases. In this form of engagement, young children are able to develop and sustain play episodes, particularly where they are familiar and friendly with their play partner. Young children playing in peer dyads are the most common grouping for convergent play to occur, although the exclusivity of this grouping may appear to contradict practitioners' pro-social agendas.